Dissemination Application for Early Warning in a Community - Tora Fahrudin; Kastaman Kastaman (IJAIT (International Journal of Applied Information Technology), 2020)
The development of sensor technology for early warning at an affordable price makes it possible to be implemented in the community. Therefore, an application is needed to send this early warning information to community members and warning response centers in real-time by considering the distance from the location of the incident. So, in this research, we proposed a dissemination application for early warning in a community (DissApps). The application was build using Code Igniter Framework, MySQL database, Mapquests, and Wablas API. This application can be used for disseminating emergency response situations such as thievery, a natural disaster such as earthquake, flood, forest fire.